Molecular Cloning of phd1 and Comparative Analysis of phd1, 2, and 3 Expression in Xenopus laevis - Dandan Han; Luan Wen; Yonglong Chen (The Scientific World Journal)
Intensive gene targeting studies in mice have revealed that prolyl hydroxylase domain proteins (PHDs) play important roles in murine embryonic development; however, the expression patterns and function of these genes during embryogenesis of other vertebrates remain largely unknown. Here we report the molecular cloning of phd1 and systematic analysis of phd1, phd2, and phd3 expression in embryos as well as adult tissues of Xenopus laevis. All three phds are maternally provided during Xenopus early development. The spatial expression patterns of phds genes in Xenopus embryos appear to define a distinct synexpression group. Frog phd2 and phd3 showed complementary expression in adult tissues with phd2 transcription levels being high in the eye, brain, and intestine, but low in the liver, pancreas, and kidney. On the contrary, expression levels of phd3 are high in the liver, pancreas, and kidney, but low in the eye, brain, and intestine. All three phds are highly expressed in testes, ovary, gall bladder, and spleen. Among three phds, phd3 showed strongest expression in heart.